Emotion analysis in socially unacceptable discourse - Jasmin Franza; Bojan Evkoski; Darja Fišer (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2022)
Texts often express the writer’s emotional state, and it was shown that emotion information has potential for hate speech detection and analysis. In this work, we present a methodology for quantitative analysis of emotion in text. We define a simple, yet effective metric for an overall emotional charge of text based on the NRC Emotion Lexicon and Plutchik’s eight basic emotions. Using this methodology, we investigate the emotional charge of content with socially unacceptable discourse (SUD), as a distinct and potentially harmful type of text which is spreading on social media. We experiment with the proposed method on a corpus of Facebook comments, resulting in four datasets in two languages, namely English and Slovene, and two discussion topics, LGBT+ rights, and the European Migrants crisis. We reveal that SUD content is significantly more emotional than non-SUD comments. Moreover, we show differences in the expression of emotions depending on the language, topic, and target of the comments. Finally, to underpin the findings of the quantitative investigation of emotions, we perform a qualitative analysis of the corpus, exploring in more detail the most frequent emotional words of each emotion, for all four datasets. The qualitative analysis shows that the source of emotions in SUD texts heavily depends on the topic of discussion, with substantial overlaps between languages.